2019
DOI: 10.1017/sjp.2019.47
|View full text |Cite
|
Sign up to set email alerts
|

Executive Control on Memory Test Performance across Life: Test of Memory Strategies

Abstract: The ability to generate memory strategies is a key factor in performance of episodic memory tests. There is evidence about the inefficient use of memory strategies in old adults. However, a question remains unresolved: Worse performance on memory test in the older people is due to an inability to mobilize cognitive strategies or to an episodic memory deficit? In this study we tried to answer it by using the Test of Memory Strategies (TMS), which parametrically reduces the need of executive functions on memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 30 publications
3
4
0
Order By: Relevance
“…Consistent with the established theories of discrete memory systems, and the original framing of the AI as an instrument capable of differentiating episodic and semantic recollection, we predicted that episodic memory measures would be positively correlated with the internal detail metrics on the AI and semantic measures would positively correlate with external details. We also predicted that executive function measures would be positively correlated with internal details and negatively correlated with external details, consistent with previous work highlighting the role of executive function in the search and retrieval of episodic memories (Abellán-Martínez et al, 2019;Conway & Pleydell-Pearce, 2000;Yubero et al, 2011).…”
Section: (Iii) Convergent Validity Of the Autobiographical Interviewsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with the established theories of discrete memory systems, and the original framing of the AI as an instrument capable of differentiating episodic and semantic recollection, we predicted that episodic memory measures would be positively correlated with the internal detail metrics on the AI and semantic measures would positively correlate with external details. We also predicted that executive function measures would be positively correlated with internal details and negatively correlated with external details, consistent with previous work highlighting the role of executive function in the search and retrieval of episodic memories (Abellán-Martínez et al, 2019;Conway & Pleydell-Pearce, 2000;Yubero et al, 2011).…”
Section: (Iii) Convergent Validity Of the Autobiographical Interviewsupporting
confidence: 88%
“…AM supports or is linked to an array of non-mnemonic constructs including executive function, depression symptoms, temporal discounting, social cognition, and facets of personality. Executive function supports episodic memory retrieval (Abellán-Martínez et al, 2019; Conway & Pleydell-Pearce, 2000; Yubero et al, 2011), low mood has been linked to less episodic specificity (Brittlebank et al, 1993; Hitchcock et al, 2014; Kuyken & Dalgleish, 1995; Liu et al, 2013; Williams & Broadbent, 1986; Williams & Scott, 1988; Williams et al, 2007; Wilson & Gregory, 2018), social cognition and AM depend on the same underlying system (Buckner & Carroll, 2007; Buckner et al, 2008; Gaesser, 2013; Gaesser & Schacter, 2014; DuPre et al, 2016; Rabin et al, 2010; Spreng et al, 2009; Spreng & Grady 2010; Spreng & Mar, 2012), and personality measures have been associated with autobiographical experience and expression (Adler et al, 2007; McAdams et al, 2004; Rasmussen & Berntsen, 2010; Rubin & Siegler, 2004). Yet these have not yet been evaluated in relation to the AI.…”
mentioning
confidence: 99%
“…There are numerous evidence that older adults have difficulties to implement internal strategies when assessing strategy use with concurrent or retrospective self-reports during a given memory task (Dunlosky & Hertzog, 2001;Froger, Bouazzaoui, Isingrini, & Taconnat, 2012;Hertzog, McGuire, Horhota, & Jopp, 2010;Hertzog, McGuire, & Lineweaver, 1998; but see Bailey, Dunlosky, & Hertzog, 2009 for different results) or self-report questionnaires about strategies used in everyday life (Bouazzaoui et al, 2010;Frankenmolen, Fasotti, Kessels, & Oosterman, 2018;Guerrero Sastoque et al, 2019). Several studies using either a direct (strategy assessment during a memory task; Abellán-Martínez et al, 2019;Bryan, Luszcz, & Pointer, 1999;Parkin & Walter, 1992;Souchay & Isingrini, 2004;Taconnat et al, 2006Taconnat et al, , 2007Taconnat et al, , 2009 or indirect (self-report of strategy use in daily life; Bouazzaoui et al, 2010) self-report measures of strategy use have shown that the age-related decline in internal strategy use is explained by the age-related deterioration of control processes.…”
Section: Control Processes and Internal Strategy Usementioning
confidence: 99%
“…The cognitive function typically deteriorates as we age. As a result, this decline will impact the daily life of old people [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…TBT can be classified into Single Task (ST) and Dual Task (DT). Some studies have proven that DT training was effective to improve balance and gait [ 1 , 2 ]. It can reduce fall risk for elder people in a real life situation, and it also helps elder people to improve their walking speed [ 1 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%